Effectiveness of Concept Mapping Strategy on Achievement in Biology among Secondary school students - P, Divya; R, Smitha (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigates the Concept Mapping strategy on achievement in biology among secondary school students. Concept Mapping would be an excellent strategy to enable the students to think about connections between science terms being learned, organize their thoughts, visualize relationships between key concepts in a systematic way and reflect on their understanding. The design for this study was a two-group Pretest Posttest quasi-Experimental. The sample consisted of IXth standard students selected from an Aided school of Palakkad District, Kerala. Instructional materials based on Concept mapping strategy was prepared and used to teach the experimental group. The data collected were analyzed using t- test and ANCOVA statistical analysis. In this study, Concept mapping was assessed as an instructional strategy for use in secondary school students in learning biology concepts. The result of the present study indicates that Concept mapping strategy is significantly more effective than the Conventional method in the improvement of achievement in Biology.